PREDATORY PRICING: SINGLE- FIRM DOMINANCE, EXCLUSIONARY ABUSE AND PREDATORY PRICES (PART 2) - Jan Louis van Tonder (Obiter, 2021)
Important pronouncements of legal principle were recently made by the Competition Appeal Court and Constitutional Court on the determination of predatory pricing under section 8 of the Competition Act 89 of 1998. These pronouncements must now be seen in the context of the subsequent commencement of certain provisions of the Competition Amendment Act 18 of 2018, which affect predatory pricing cases under section 8 of the Act. In light of these developments, the main aim of this series of three articles is to evaluate the law relating to the economic concept of predatory pricing under the Competition Act. In this context, the main constituent elements of a predatory pricing case – namely dominance, identifying an exclusionary abuse, and predatory prices – are discussed in three parts. Part 1 has critically evaluated the law on the determination of single-firm dominance under section 7 of the Competition Act. Part 2 starts to focus on the abuse analysis and discusses the basic forms of abuse, the meaning of abuse, tests that have been developed to identify exclusionary abuse, the criticism of the traditional theory of predatory pricing, the main strategic economic theories of predatory pricing and non-pricing theories of predation. Part 3 then specifically deals with the law of predatory prices under section 8(c) and (d)(iv) of the Competition Act. Pursuant to section 1(3) of the Competition Act, when interpreting or applying the Competition Act, appropriate foreign and international law may be considered. This is complementary to section 1(2)(a), which directs that the Competition Act must be interpreted in a manner that is consistent with the Constitution and gives effect to the purposes set out in section 2. In light hereof, where appropriate, the South African position is mainly compared with the position in the European Union and the United States.